2020
DOI: 10.1016/j.bbi.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status of medical staff in emergency departments during the Coronavirus disease 2019 epidemic in China

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
176
11
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 246 publications
(226 citation statements)
references
References 22 publications
24
176
11
15
Order By: Relevance
“…Previous studies showed that exposure to a public health emergency can cause mental health problems, depression and even PTSD [13,29,30]. However, results of the present study showed that the psychological status of the participants was not bad and most mental health scores were in the uppermiddle range, which is also inconsistent with some recent studies [12,31,32]. The reason for the difference may be that the study was conducted in different periods and regions.…”
Section: In Uencing Factors For Coping Ability and Mental Health Statuscontrasting
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that exposure to a public health emergency can cause mental health problems, depression and even PTSD [13,29,30]. However, results of the present study showed that the psychological status of the participants was not bad and most mental health scores were in the uppermiddle range, which is also inconsistent with some recent studies [12,31,32]. The reason for the difference may be that the study was conducted in different periods and regions.…”
Section: In Uencing Factors For Coping Ability and Mental Health Statuscontrasting
confidence: 99%
“…This study was conducted in the early stage of the epidemic in Henan Province, and Henan Province did not experience a large-scale spread of the epidemic and took timely countermeasures. In line with previous studies, age, participation in the event, health condition and trust in uno cial information were the main in uencing factors to mental health [12,31,[33][34][35]. Contrary to a recent study, age worked as a facilitating factor to mental health.…”
Section: In Uencing Factors For Coping Ability and Mental Health Statussupporting
confidence: 82%
See 2 more Smart Citations
“…China is the first country to be severely affected by COVID-19, and the mental health of Chinese frontline medical staff has been greatly affected. A considerable proportion of Chinese healthcare workers have reported symptoms of depression (25.2%-58%), anxiety (29.18%-54.2%), or insomnia (34.0%-36.1%) during the COVID-19 epidemic [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%